Advancing understanding of Ficus carica: a comprehensive genomic analysis reveals evolutionary patterns and metabolic pathway insights - Bao, Yuting; He, Miaohua; Zhang, Chenji; Jiang, Sirong; Zhao, Long; Ye, Zhengwen; Sun, Qian; Xia, Zhiqiang; Zou, Meiling (Frontiers in Plant Science, 2023)
Ficus carica L. (dioecious), the most significant commercial species in the genus Ficus, which has been cultivated for more than 11,000 years and was one of the first species to be domesticated. Herein, we reported the most comprehensive F. carica genome currently. The contig N50 of the Orphan fig was 9.78 Mb, and genome size was 366.34 Mb with 13 chromosomes. Based on the high-quality genome, we discovered that F. carica diverged from Ficus microcarpa ~34 MYA, and a WGD event took place about 2─3 MYA. Throughout the evolutionary history of F. carica, chromosomes 2, 8, and 10 had experienced chromosome recombination, while chromosome 3 saw a fusion and fission. It is worth proposing that the chromosome 9 experienced both inversion and translocation, which facilitated the emergence of the F. carica as a new species. And the selections of F. carica for the genes of recombination chromosomal fragment are compatible with their goal of domestication. In addition, we found that the F. carica has the FhAG2 gene, but there are structural deletions and positional jumps. This gene is thought to replace the one needed for female common type F. carica to be pollinated. Subsequently, we conducted genomic, transcriptomic, and metabolomic analysis to demonstrate significant differences in the expression of CHS among different varieties of F. carica. The CHS playing an important role in the anthocyanin metabolism pathway of F. carica. Moreover, the CHS gene of F. carica has a different evolutionary trend compared to other Ficus species. These high-quality genome assembly, transcriptomic, and metabolomic resources further enrich F. carica genomics and provide insights for studying the chromosomes evolution, sexual system, and color characteristics of Ficus.